C─C Cleavage Approach to C─H Functionalization of Saturated Aza-Cycles - Roque, Jose B. (ACS Catal, 2020)
Saturated cyclic amines (aza-cycles) are ubiquitous structural motifs found in pharmaceuticals, agrochemicals, and bioactive natural products. Given their importance, methods that directly functionalize aza-cycles are in high demand. Herein, we disclose a fundamentally different approach to functionalizing cyclic amines which relies on C─C cleavage and attendant cross-coupling. The initial functionalization step is the generation of underexplored N-fused bicyclo α-hydroxy-β-lactams under mild, visible light conditions using a Norrish–Yang process to affect α-functionalization of saturated cyclic amines. This approach is complementary to previous methods for the C─H functionalization of aza-cycles and provides unique access to various cross-coupling adducts. In the course of these studies, we have also uncovered an orthogonal, base-promoted opening of the N-fused bicyclo α-hydroxy-β-lactams. Computational studies have provided insight into the origin of the complementary C─C cleavage processes.